Synthesis of biodiesel and prepared its blend: An ecofriendly, clean, alternative, and sustainable energy source - Madhuri A. Balpande; Manish M. Katiya; Madhukar G. Dhonde; Jayant M. Gajbhiye (Tetrahedron Green Chem)
A base catalyzed the transesterification reaction, resulting in a 98 % yield during biodiesel (fatty acid methyl ester - FAME) synthesis. The optimization reaction protocol requires maximum agitation of 600 rpm at room temperature for 20min with a 10mol% KOH as a base catalyst and 1:8 ratios of sunflower oil and methanol to complete the reaction. This study examines the viability of using vegetable oil through transesterification to produce biodiesel on a commercial scale, with the goal of serving as a fuel substitute for diesel engines. We explored well-established spectroscopic techniques, including Infra-Red, 1H, 13C Nuclear Magnetic Resonance, Gas Chromatography Mass Spectra, and High-Resolution Mass Spectra, to investigate the synthesized FAME in accordance with the ASTM specification. The novelty of the current study outlines the significance of synthesizing FAME through catalytic transesterification, examines its physicochemical parameters, and green chemistry matrices have shown that biodiesel is a beneficial fuel, which led to less reaction waste, better environmental compatibility, and long-term use of the current protocol. In addition to exploring biodiesel's fuel applications; we are also looking into its possible uses as a biodetergent for other purposes and a biolubricant for diesel engines. The study highlights the simple, efficient development of current biodiesel, with its sustainability, and its potential contribution to renewable energy goals. It also explores the environmental impact of transitioning to biobased alternatives and its potential applications in industries like cosmetics and automobiles. Therefore, this investigation aims to explore and combine the unique advantages associated with varying ratios of additives in FAME, with the goal of replacing as much diesel as possible. We created and experimented with blends including 10, 20, and 30 % ethanol or iso-octane in FAME; nevertheless, the blend containing 30 % ethanol works better as a diesel substitute.